The Effectiveness of Steam Digitalization in Slow Pedagogy: Building Early Childhood Literacy Through Malay Culture - Suharni Suharni; Sean Marta Efastri; Lucky Lhaura Van FC (Postgraduate, University of Mataram, 2025)
Developing early childhood literacy requires innovative and contextual learning approaches that integrate technology and local cultural values. This study aims to analyze the effectiveness of STEAM digitalization within a slow pedagogy framework to enhance literacy skills among early childhood learners by incorporating Malay cultural elements into the learning process. The proposed solution is the implementation of a digitalized STEAM-based learning model supported by interactive multimedia, designed to create meaningful, engaging, and culturally relevant learning experiences. This research employed a quantitative experimental design involving two groups of early childhood students: an experimental group receiving instruction through digitalized STEAM-based slow pedagogy and a control group using conventional teaching methods. The study involved 60 children selected through purposive sampling. Data were collected using literacy performance tests, observation sheets, and teacher assessments. The findings indicate that the implementation of STEAM digitalization in slow pedagogy significantly improved children's literacy achievement. Results of the paired sample t-test show a significant difference between pre-test and post-test scores in the experimental group (t = 8.412; p < 0.05), demonstrating the effectiveness of the approach. Furthermore, the independent sample t-test revealed a significant difference between the experimental and control groups (t = 2.132; p < 0.05). The study concludes that STEAM digitalization combined with slow pedagogy is an effective strategy for enhancing early childhood literacy while promoting Malay cultural identity. It is recommended that culturally grounded and interactive digital STEAM resources be integrated into early childhood education to foster sustainable and meaningful literacy development